Pengaruh Budaya Organisasi Dan Kepuasan Kerja Terhadap Kinerja Karyawan Dengan Organizational Citizenship Behavior (OCB) Sebagai Variabel Intervening Pada PT. Pos Indonesia (Kantor Pusat Mataram) - Hany Pebrianti; Isra Dewi Kuntary Ibrahim; Irwan Cahyadi (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2023)
This study aims to examine the effect of organizational culture and job satisfaction on employee performance with organizational citizenship behavior (OCB) as an intervening variable at PT. Pos Indonesia (Mataram Head Office). The population in this study are employees of PT. Pos Indonesia, totaling 92 people. The sample in this study used the census method, namely the entire population was used as a sample of 92 people. This type of research is quantitative using a causality approach. The analysis used is SEM analysis and data analysis techniques using the SmartPLS 3.0 program. The results of this study indicate that organizational culture and job satisfaction have a positive and significant effect on OCB. Organizational culture and job satisfaction have a positive and significant effect on employee performance. OCB has a positive and significant effect on employee performance. Organizational culture and job satisfaction have a positive and significant effect on employee performance with OCB as the intervening variable. Suggestions in this study is the number of employees with productive age, PT. Pos Indonesia can use these employees as a forum for finding new ideas to develop the company.